Pre-clinical and clinical studies of a novel porous biphasic calcium phosphate ceramic as alternative to repair bone defects - Machado, Ricardo Quirico Pinheiro (2019)
Objectives: We compared a novel porous biphasic calcium phosphate (pBCP) containing 70% HA and 30% -TCP with autogenous bone (AB) regarding bone formation, graft granular size influence (0.7, 1.0 or 1.5 mm), physicochemical properties, and volumetric changes of the total grafted area as well its components (newly formed bone, graft particle stability and soft tissue). Materials and methods: Article 1 used a critical size defect in rats. Analyzes included XRD (X-ray diffraction), SEM (scanning electron microscope) and EDS (Energy-dispersive X-ray spectroscopy) in vitro and then histomorphometry of biopsies collected from rat skull. Article 2 used a bilateral MSFA by lateral wall surgery in 12 patients in a split-mouth design. Analyses of three-dimensional (3D) cone beam computed tomography (CBCT) scans at different periods (T0, T1 and T2), and of micro-CT scans and histological slides of graft core biopsies were performed. Results: In the preclinical approach, similar physicochemical characteristics among pBCPs with different granular sizes were found. Besides, osteopromotion regarding pBCP granular sizes of 0.7 and 1.0 were higher than AB. In the clinical approach, pCBP was similar to AB. However, in both approaches, the volume of the total grafted area and particles within the grafted area were more reduced for AB (45% and 37%, respectively, in article 1 and 31% and 33%, respectively, in Article 2). For pBCP these volumetric changes did not occur, except for 1.5 mm size group in the preclinical approach, which showed a significant reduction in the last period (24 weeks). Conclusion: pBCP70:30 physicochemical characteristics, such as slow resorption, creates a favorable microenvironment for bone formation that is directly influenced by the granule size. pBCP70:30 promotes greater preservation of the grafted volume than AB, thus being a good alternative for MSFA and bone regeneration procedures.